2008
DOI: 10.1002/car.1044
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations from child fatality review teams: results of a US nationwide exploratory study concerning maltreatment fatalities and social service delivery

Abstract: Multidisciplinary child fatality review teams (CFRT) have existed in the United States (US) for almost 30 years; the products of the review process, however, remain unexamined. This study reviewed reports from CFRT throughout the US to compile and evaluate the identification of problems and recommendations by professionals concerning child maltreatment fatalities. Team-and state-level data were also used for analysis to better understand the context in which recommendations are made. Over 300 recommendations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…? ) The third paper in this themed issue is by Emily Douglas and Jennifer Cunningham (Douglas and Cunningham, 2008) who discuss the work of the US equivalent of the English SCR, the Child Fatality Review Team (CFRT). Douglas and Cunningham studied CFRT reports published from 2000-07.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…? ) The third paper in this themed issue is by Emily Douglas and Jennifer Cunningham (Douglas and Cunningham, 2008) who discuss the work of the US equivalent of the English SCR, the Child Fatality Review Team (CFRT). Douglas and Cunningham studied CFRT reports published from 2000-07.…”
mentioning
confidence: 99%
“…high turnover and dissatisfaction' (Douglas and Cunningham, 2008, DOI: 10.1002/car.1044) indicate that practitioners in the US are operating under some of the same pressures as their UK colleagues. The authors highlight the 'problems that plague the professions that respond to child maltreatment' and 'the failures of the nation's social service system' (Douglas and Cunningham, 2008, DOI: 10.1002/car.1044. This suggests that the issues and pressures they have identified may be rooted-as they are in the UK-in more fundamental problems in the child protection system.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…139]. Reviews of (near) fatal CAN cases have demonstrated practice failings, including inadequate inter-organisational communication and information-sharing [160,161]. Integrating information held by various professionals on, for example, signs, risk factors or critical events can result in a more comprehensive view of the child's situation.…”
Section: Introductionmentioning
confidence: 99%